2011
DOI: 10.4187/respcare.00853
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia Adds to the CURB-65 Pneumonia Severity Score in Hospitalized Patients With Mild Pneumonia

Abstract: the Neumonía Adquirida en la Comunidad de la Comunidad Valenciana Study Group BACKGROUND: Hypoxemia may influence the prognosis of patients with mild pneumonia, regardless of the initial CURB-65 score (confusion, blood urea nitrogen > 20 mg/dL, respiratory rate > 30 breaths/min, blood pressure < 90/60 mm Hg, and age > 65 y). OBJECTIVE: To determine the risk factors associated with hypoxemia and the influence of hypoxemia on clinical outcomes in hospitalized patients with mild pneumonia. METHODS: We performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
(37 reference statements)
4
20
0
Order By: Relevance
“…Hypoxemia and clinical judgment determined hospital admission in these patients. Indeed, 47.5% of CURB‐65 0–1 patients showed PaO 2 /FiO 2 <300 as we have published previously …”
Section: Discussionsupporting
confidence: 74%
“…Hypoxemia and clinical judgment determined hospital admission in these patients. Indeed, 47.5% of CURB‐65 0–1 patients showed PaO 2 /FiO 2 <300 as we have published previously …”
Section: Discussionsupporting
confidence: 74%
“…First, the presence of dyspnea was an independent prognostic factor. This is in accordance with previous studies in which hypoxemia was found to be an independent prognostic factor in patients with pneumonia (15,16). In the present study, dyspnea correlated significantly with the PaO2/FiO2 ratio and the respiratory rate (r=-0.380, p<0.001; r=0.345, p<0.001, respectively).…”
Section: Discussionsupporting
confidence: 82%
“…This severity of illness indicator was not routinely used in our emergency department during the study period, and the majority of patients hospitalized with CAP had a score or 0 or 1. Moreover, nearly 30% had both a low CURB-65 score and absence of a new oxygen requirement, a marker of severity of illness that the CURB-65 score does not take into account [18]. Although social factors and/or comorbid conditions likely influenced the decision to hospitalize in some cases [19], admission may have been avoided in at least a subset of patients by using the CURB-65 score as an adjunct in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%